PENINGKATAN PRESTASI BELAJAR DAN MENUMBUHKEMBANGKAN MINAT KEWIRAUSAHAAN PADA SISWA KELAS III TP-4 SMK WIWOROTOMO MELALUI PEMBELAJARAN BERBASIS KOMPETENSI - Susilo Susilo (Sainteks, 2011)
The aim of the classroom action research is to improve the learning achievement and entrepreneurship interests of the students of SMK majoring Mechanical engineering. This research was conducted at even semester of class III TP-4 students of Wiworotomo Vocational School of Purwokerto Central Java in the academic year 2009 - 2010. The result of the classroom action research are (1) the improvement of the students’learning achievement in Complex of turn-work. The mean of the result of activity in cycle I was 8,19 and in cycle II increased into 8,98. (2) the improvement of the students’ entrepreneurship interest was 30,29%. From the result of the questionaires in cycle I the students’ entrepreneurship interest was 3,04% and cycle II increase into 33,33%. Keywords: Complex of turn-work, Enthusiasm entrepreneurship, Study base on